2022
DOI: 10.1002/hed.26985
|View full text |Cite
|
Sign up to set email alerts
|

Prospective longitudinal study on fear of cancer recurrence in patients newly diagnosed with head and neck cancer: Course, trajectories, and associated factors

Abstract: Background This study assessed the course of fear of cancer recurrence (FCR) in patients newly diagnosed with head and neck cancer (HNC), identified FCR trajectories and factors associated with FCR trajectories. Methods Six hundred and seventeen HNC patients from the NET‐QUBIC cohort study completed the Cancer Worry Scale‐6 at diagnosis, 3 and 6 months post‐treatment. FCR trajectories were identified using Latent Class Growth Analysis. Associations were explored between FCR trajectories and baseline demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Previously, we conducted a meta-analysis study on factors associated with FCR, which confirmed that FCR may be strongly associated with the occurrence of anxiety and depression, increased fatigue, and decreased well-being and quality of life in cancer survivors [ 7 ]. In addition, longitudinal studies have shown that while FCR may decline slightly over time, approximately 20% of cancer survivors experience persistently high FCR, and even 10 years after a cancer diagnosis, FCR remains a dominant psychological health problem for survivors [ 8 , 9 ]. Therefore, it is particularly important to explore the triggers and coping strategies of FCR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we conducted a meta-analysis study on factors associated with FCR, which confirmed that FCR may be strongly associated with the occurrence of anxiety and depression, increased fatigue, and decreased well-being and quality of life in cancer survivors [ 7 ]. In addition, longitudinal studies have shown that while FCR may decline slightly over time, approximately 20% of cancer survivors experience persistently high FCR, and even 10 years after a cancer diagnosis, FCR remains a dominant psychological health problem for survivors [ 8 , 9 ]. Therefore, it is particularly important to explore the triggers and coping strategies of FCR.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the current studies on FCR are quantitative [ 7 , 8 , 9 ]. However, because FCR is recognized as a unique, independent, and multidimensional structure with its own characteristics and mechanisms, targeted interventions need to be constructed.…”
Section: Introductionmentioning
confidence: 99%
“…Change trajectories in previous research involved numerically small groups, and failure to replicate these may reflect inherent difficulties in reliably detecting trajectories with low numbers (Nasserinejad et al, 2017). We note that other studies have not found them (Costa et al, 2019;Duening-Smit et al, 2022;Gonzales et al, 2017;McGinty et al, 2016;Shim et al, 2020;Yang et al, 2018). Also, we predominantly made yearly observations and may have missed any rapid changes.…”
Section: Discussionmentioning
confidence: 84%
“…McGinty et al (2016) found that breast cancer patients with higher FCR trajectories had lower baseline self-efficacy, higher perceptions of illness risk, and increased reassurance seeking. Duening-Smit et al (2022) found that higher FCR trajectories in head and neck cancer patients were related to lower self-efficacy, higher passive coping and self-reassurance scores, and lower avoidance scores. Gonzales et al (2017) found that baseline withholding of concerns and greater pain medication use in gynecological cancer patients predicted depression, poorer quality of life, and disability.…”
mentioning
confidence: 89%
“…Taking into account the growing number of cancer survivors, from a practical and economical point of view, but also from the perspective of the patients, HCP's and the organizational context, the combination of a first universal step of normalizing FCR in consultations with the doctor or nurse followed by matched care for those experiencing elevated feelings of FCR [3 ▪▪ ] might be most feasible to implement. This approach is supported by trajectory studies indicating a large group of patients experiencing low levels of FCR over time [28,29] a large group of patients experiencing moderate and fluctuating FCR over time [29], and a smaller proportion experiencing continuous high FCR over time [28,29] all benefitting from normalizing FCR and those with moderate or high FCR in need of matched supportive care [29].…”
Section: Current Challengesmentioning
confidence: 94%